Peran Konselor dalam Meningkatkan Keterampilan Sosial Anak Underachiever Melalui Media ATM Dongeng - Pratama, Beny Dwi; Kadafi, Asroful; Suharni, Suharni (STKIP Muhammadiyah Pringsewu, 2019)
Field findings indicate that many underachiever children have low social skills, one of which is found in Nambak Bungkal Elementary School Ponorogo. Low social skills, seen from the lack of ability to cooperate, lack of ability to adapt, have not been able to interact positively, have not been able to control themselves, have not been able to develop an attitude of empathy for friends, do not have the ability to obey the rules, and have not been able to respect others. From this case, this study aims to improve the social skills of underachiever children. Strategies to improve social skills in this study through the use of fairy tale ATM media. This research design uses a quantitative approach, precisely quasi-experiment. The sampling technique was carried out by purposive sampling. The results of the study are seen from the data analysis using Wilcoxon questions showing Z value of -2.207 with p value (Asymp. Sig 2 tailed) of 0.027 which is less than the critical limit of the study of 0.05 so the hypothesis is to accept H1 or meaning there are significant differences between pretest and posttest groups, meaning that there is an increase in underachiever students' social skills. This proves that the Fairy Tale ATM media can be used as a service medium to help improve the underachiever's social skills. From the results of this study, it is expected that Counselors can collaborate with classroom teachers in providing treatment to students with special needs to optimize the potential possessed by students. ABSTRAKTemuan dilapangan menunjukan bahwa banyak anak underachiever yang memiliki keterampilan social rendah, salah satunya terdapat di SD Negeri Nambak Bungkal Ponorogo. Keterampilan social rendah, terlihat dari kurangnya kemampuan bekerjasama, kurang mampu menyesuaikan diri, belum mampu berinteraksi secara posistif, belum mampu mengontrol diri, belum mampu mengembangkan sikap empati terhadap teman, belum memiliki kemampuan dalam menaati aturan, serta belum mampu menghargai orang lain. Dari kasus tersebut, penelitian ini bertujuan untuk meningkatkan ketrampilan sosial anak underachiever. Strategi dalam meningkatkan keterampilan sosial dalam penelitian ini melalui pemanfaatan media ATM dongeng. Desain penelitian ini menggunakan pendekatan kuantitaif, tepatnya quasi-eksperimen. Teknik pengambilan sampel dilakukan dengan purposive sampling. Hasil penelitian dilihat dari analisa data menggunakan perhitingan wilcoxon menunjukan nilai Z sebesar -2,207 dengan p value (Asymp. Sig 2 tailed) sebesar 0,027 di mana kurang dari batas kritis penelitian 0,05 sehingga keputusan hipotesis adalah menerima H1 atau yang berarti terdapat perbedaan bermakna antara kelompok pretest dan posttest, artinya terdapat peningkatan keterampilan sosial siswa underachiever. Hal ini membuktikan jika media ATM Dongeng terbukti dapat digunakan sebagai media layanan untuk membantu meningkatkan keterampilan social siswa underachiever. Dari hasil penelitian ini, diharapkan Konselor dapat berkolaborasi dengan Guru kelas dalam memberikan treatment pada siswa berkebutuhan khusus untuk mengoptimalkan potensi yang dimiliki oleh siswa.